Mendidik Ilmuwan yang Bertanggung Jawab: Pentingnya Etika dalam Pembelajaran Biologi - Salsadita, Indira Ruly; Liza, Nasywa; Azzahra, Tiara Alifia; Suryanda, Ade (Pendagogia: Jurnal Pendidikan Dasar, 2024)
Biology as a subject that explores living things and their environment will never be separated from any issues related to norms and ethics. In every development there will always be issues that can be related to ethical issues. Ethics is a boundary that causes a right/wrong assessment of every human behavior. Therefore, this article is written to examine ethics in biology learning to educate future responsible scientists. The method used in this research is descriptive with a library research approach. The data collection technique used is to search and collect reading sources from journals/articles that have been published before. The sources that have been collected are then analyzed to obtain the desired information. The results obtained are that in its implementation, biology education is not only required to provide learning related to theory but also related to biological ethics or also known as bioethics. The reason is, because biology is a branch of science that is directly related to living things and their environment, so it is necessary to have restrictions so that humans also still have a sense of responsibility.